2007
DOI: 10.1128/jvi.02642-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fusion Determinants Points to the Involvement of Three Discrete Regions of Both E1 and E2 Glycoproteins in the Membrane Fusion Process of Hepatitis C Virus

Abstract: Infection of eukaryotic cells by enveloped viruses requires the merging of viral and cellular membranes.Highly specific viral surface glycoproteins, named fusion proteins, catalyze this reaction by overcoming inherent energy barriers. Hepatitis C virus (HCV) is an enveloped virus that belongs to the genus Hepacivirus of the family Flaviviridae. Little is known about the molecular events that mediate cell entry and membrane fusion for HCV, although significant progress has been made due to recent developments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
193
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(206 citation statements)
references
References 65 publications
(117 reference statements)
11
193
1
1
Order By: Relevance
“…These mutations reside within three discrete regions, one located in E1 and two located in E2. Interestingly, HCVpp harboring mutant E2 proteins with a single mutation of a highly conserved glycine at position 418 to alanine or aspartic acid (G418A; G418D) were heavily impaired with regard to infectivity and cell-cell fusion capacity, but they exhibited different fusion behaviors depending on whether Gly-418 had been mutated to Ala or Asp (25). We therefore introduced such mutations in the Jc1 context and analyzed glycoprotein processing and release of HCV particles, as well as their infectivity and fusion properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These mutations reside within three discrete regions, one located in E1 and two located in E2. Interestingly, HCVpp harboring mutant E2 proteins with a single mutation of a highly conserved glycine at position 418 to alanine or aspartic acid (G418A; G418D) were heavily impaired with regard to infectivity and cell-cell fusion capacity, but they exhibited different fusion behaviors depending on whether Gly-418 had been mutated to Ala or Asp (25). We therefore introduced such mutations in the Jc1 context and analyzed glycoprotein processing and release of HCV particles, as well as their infectivity and fusion properties.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together these data further confirm that the HCVcc-liposome fusion assay is dependent upon the HCV E2 glycoprotein. Single Mutation in E2 Leads to a Severe Impairment of Jc1 Infectivity and Fusion-We recently showed that specific point mutations introduced in the sequence of E1 or E2 led to severe defects in HCVpp infectivity and membrane fusion without affecting HCVpp production and incorporation of E1-E2 complexes into HCVpp (25). These mutations reside within three discrete regions, one located in E1 and two located in E2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusion between the two cell lines results in the appearance of green syncytia. Variants of this system, using on one hand the luciferase reporter gene under the control of the HIV-1 promoter and the Tat transactivator on the other hand have also been developed [118,119]. Another experimental setup relies on inducing virus fusion at the cell surface ( Figure 6B) [78,104].…”
Section: Endocytosis and Fusion Of Hcvmentioning
confidence: 99%
“…Clathrin-dependent endocytosis -Internalization assay [146] -Inhibition by drugs and dominant-negative mutants -Live cell microscopy with labelled HCV [154] Low pH-mediated fusion in early endosomes -Inhibitors of endosomal acidi cation -Di erent fusion assays (see main text) Attachment and receptor interaction -Cell binding assays (CHO-SR-BI, CHO-CD81, etc) [118] -Pull-down assays [152] or ELISAs [132,153] with soluble CD81 or with heparin -Cell lines for receptor complementation (see Table 1) -Lentiviral expression vectors for the 4 speci c receptors and their homologs [104,116] H + Concanamycin A, Bafilomycin A1, Chloroquine, NH 4 Cl [69,146,147] Rab5 dominant negative mutant [145,146] Eps15 dominant negative mutant, Clathrin heavy chain siRNAs, Chlorpromazine [78,[145][146][147] Abs, Ezetimibe [32] NPC1L1 EGFR…”
Section: Highly Specific Receptors Initial Attachment Factorsmentioning
confidence: 99%